Prevalence and morbidity of urogenital schistosomiasis among pre-school age children in Cubal, Angola. - Raquel Sánchez-Marqués; Cristina Bocanegra; Fernando Salvador; Arlette Nindia; Zeferino Pintar; Joan Martínez-Campreciós; Sandra Aixut; Patricia Mossalilo; Elena Sulleiro; María Espiau; Santiago Mas-Coma; Ma Dolores Bargues; et al. (Public Library of Science (PLoS), 2023)
Background Schistosomiasis is one of the most important neglected tropical diseases, with a great impact on public health and more than 200,000 deaths annually. Schistosoma haematobium causes urinary tract (UT) morbidity. Since schistosomiasis morbidity control programs focus on children older than 5 years, pre-school age children (PSAC) morbidity is not well known. Methods We conducted a cross-sectional study in Cubal (Angola) among 245 PSAC with the objective of evaluating the prevalence of S. haematobium infection, the intensity of infection, and associated morbidity. For this purpose, urine filtration test followed by microscopic visualization and ultrasound examinations were performed. Results The estimated overall prevalence of urogenital schistosomiasis was 30.2% (CI 95%; 24.5-35.9), with 20.3% (CI 95%; 15.3-25.3) of the samples analysed showing a high intensity of infection. A total of 54.5% (CI 95%; 47.6-61.8) of infected children presented UT lesions, showing a significant association between schistosomiasis infection and UT morbidity (p-value < 0.001). Bladder wall thickening was the most common lesion, being present in 100% of abnormal ultrasounds. We found that anaemia and severe malnutrition were not significantly associated with the development of UT lesions. Conclusions S. haematobium infection in PSAC causes great UT detectable morbidities. Therefore, there is an evident need of including them in mass drug administration (MDA) campaigns and consequently the development of an adapted praziquantel treatment dosage for children under 2 years of age.